Design and synthesis of antiproliferative 2-oxoindolin-3-ylidenes incorporating urea function with potential VEGFR-2 inhibitory properties - Dalia R. Aboshouk; M. Adel Youssef; Siva S. Panda; Benson M. Kariuki; Mohamed S. Bekheit; Ahmed R. Hamed; Walid Fayad; Ahmed A. F. Soliman; Adel S. Girgis (Scientific Reports)
Abstract Targeted therapy is preferable over other therapeutics due to its limitation of drawbacks and better pharmaceutical outcomes. VEGF and its receptors have been observed to be hyper-activated in many cancer types and are considered promising targets for assigning anticancer agents. The current study is directed towards synthesis of novel antiproliferative 2-oxoindolin-3-ylidenes incorporating urea function with VEGFR-2 properties. The targeted agents were obtained through a two-step reaction. Addition of the appropriate 1-(acetylphenyl)-3-phenylurea 9a,b to the corresponding isatin 10a–f in ethanol containing a quantitative amount of Et2NH followed by acidic dehydration (AcOH/HCl) afforded the targeted agents 12a–j. Promising antiproliferation properties (MTT assay) were observed for most of the synthesized agents against HCT116 (colon), MCF7 (breast) and PaCa2 (pancreatic) cancer cell lines relative to sunitinib. VEGFR-2 inhibitory properties are consistent with the antiproliferation properties exhibited against the tested cell lines. Compound 12b (R = 4-NHCONHPh, R′ = H; % inhibition = 87.2) is the most promising/potent anti-VEGFR-2 agent synthesized with activity close to that of sunitinib (% inhibition = 89.4) at 10 μM. Molecular docking studies (PDB: 3WZE and 3AGD) support the antiproliferation effects against cancer cell lines tested with VEGFR-2 inhibitory properties. The results are consistent with collaboration of the pharmacophores considered (2-oxoindolyl heterocycle and urea) in improving the bio-properties.